ANTERIOR CRUCIATE LIGAMENT TEAR FOLLOWING SURGICAL TREATMENT OF PEDIATRIC TIBIAL EMINENCE FRACTURE IN A MULTICENTER COHORT. Issue 7 (30th July 2021) - O'Donnell, Ryan; Bokshan, Steven; Brown, Kelsey; Aoyama, Julien T; Ganley, Theodore J; Fabricant, Peter D; Patel, Neeraj M.; Ellis, Henry B; Green, Daniel W; Jagodzinski, Jason E; Kushare, Indranil; Lee, R Jay; et al.
Background: While operative treatment of displaced pediatric tibial eminence fractures has generally been shown to be safe, post-operative complications including arthrofibrosis, infection, fixation failure, and postoperative ipsilateral ACL injuries remain prevalent. The purpose of this study was to describe the prevalence of and risk factors for post-operative ACL tears in a cohort of patients surgically treated for tibial eminence fracture. Methods: We performed a retrospective review of children undergoing treatment of a tibial eminence fracture at 10 tertiary children's hospitals.. The primary outcome was subsequent ACL rupture. Patients with 2 year follow up data and those that had met the primary outcome within the 2 year period, were analyzed for demographics, risk factors and survival analyses Results: 385 pediatric patients were reviewed. Overall, 46 patients had either 2 year follow up data or met the primary outcome measure of an ACL tear prior to the 2 year mark. Mean age was 11.2 years old (SD 2.8), and the median follow time was 36.4 months (SD 17.7 months) There was a 21.7% incidence of subsequent ACL tear in the cohort analyzed. Subsequent ACL tears occurred at a median of 10.2 months (SD 19.5 months) postoperatively. There was a statistically significant association with higher Myers & McKeever grade tibial spine fractures (Type III and IV) and subsequent ACL rupture ( p =0.006). Subsequent ACL tears occurred in patients who were older when they had their original tibial eminence fracture, 13.4 years old versus 11.3 years old ( p= 0.035). There was no statistically significant relationship between ipsilateral ACL tear and body mass index, operative time, fixation method used, postoperative weight bearing status, type of postoperative immobilization, contact versus non-contact injury mechanism, type of post-operative physical therapy protocol based on chi-squared or t -test ( p >0.05). Conclusion: Subsequent ipsilateral ACL tears following operatively treated pediatric tibial eminence fractures in a large multicenter cohort occurred at a rate of 21.7%. They were associated with completely displaced (Type III or IV) tibial eminence fractures, and older patients. Clinicians should therefore continue to follow patients for at least 2 years after treatment of pediatric tibial eminence fractures in order to track this potential complication.